Stress and relief of misfit strain of Ge/Si(001) - Wedler, G; Walz, J; Hesjedal, T; Chilla, E; Koch, R (1998)
The intrinsic stress of the Stranski-Krastanov system Ge/Si(001) was investigated in the range 700-1050 K. Characteristic stress features indicate that the relief of the misfit strain proceeds mainly in two steps: (i) by the formation of 3D islands on top of the Ge wetting layer and (ii) via misfit dislocations in larger 3D islands and upon their percolation. The temperature dependence of strain relief by 3D islands as well as their nucleation and growth behavior support a kinetic pathway for 3D islanding.